Foreward - Anton Wachidin Widjaja (President University, 2022)
We cordially welcome all participants to the 5th International Conference on Family Business and Entrepreneurship (ICFBE) 2021. This year's ICFBE in the COVID-19 pandemic is held hybrid, online and offline. This conference was organized by the Faculty of Business, President University, in collaboration with Universitas Dhyana Pura and Indonesia Strategic Management Society. The theme of this conference is “On the Path to Recovery: Leadership, Resilience, and Creativity”. This theme is seen as important for businesses to survive and continue to maintain their competitive position by developing resilience and innovation. The objective of ICFBE 2021 is to provide a platform for researchers, academicians, and business practitioners as well as industrial professionals to present their research and development activities in Business and Management. This conference provides opportunities for the delegates to exchange new ideas and experiences, establish business or research relations, and find global partners for future collaboration.We thank and appreciate all speakers in the ICFBE 2021. The opening remarks were given by Dr. Ir. I Wayan Koster as the Governor of Bali and the keynote speeches were given by Dr. Hariyadi Sukamdani as the Indonesian Employers' Association (Asosiasi Pengusaha Indonesia - APINDO) and General Chair of the Indonesian Hotel and Restaurant Association (PHRI). The speakers in this ICFBE were Prof. Ki-Chan Kim from the Catholic University of Korea with the topic of The Humane Entrepreneur: Desirable Business Practices; Prof. Ruth Rentschler from the University of South Australia with the topic of Resiliency and Creativity in Organizations; the founder of PT. Mandaya Sehat Utama, Dr. Edhijanto W. Taufik, and the owner of PT. Kutus Kutus Herbal, Mr. Servasius Bambang P. delivering a topic on How My Business Survived the Covid-19 Pandemic: Real Business Sharing and Experiences, Prof. Dr. Jony Oktavian Haryanto from President University with the topic of Getting Your Professorship at a Young Age, and Sari Wahyuni, Ph.D. from Indonesia Strategic Management Society with the topic of Current Trend in Qualitative Research.